Removal of Cr(VI) from Aqueous Solution using Bamboo Biomass Derived Hydro Char Prepared by Hydrothermal Carbonization - Adhikari, Purnananda; Subedi, Netra Prasad; Nyachhyon Rajbhandari, Armila; Pradhan Amatya, Sharmila; Khanal, Santosh (Amrit Journal, 2025)
Hydrochar is considered a promising adsorbent due to its low energy-intensive preparation along with its richness in surface functional groups. Herein, bamboo-derived hydrochar (BHC) was synthesized by hydrothermal carbonization at 200°C for four hours, and characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET) analysis. As-prepared bamboo hydrochar (BHC) was used as an adsorbent for the removal of Cr(VI) from aqueous solution. The effects of the solution pH, adsorbent dose, initial Cr(VI) concentration, and contact time were examined in a batch experiment method. The results revealed that effective Cr(VI) adsorption was facilitated by the mesoporous structure of BHC containing a large number of oxygen-containing surface functional groups. The equilibrium adsorption data supports the Langmuir isotherm and the maximum adsorption capacity for Cr(VI) is found to be 50.86 mg g-1 at a solution pH of 4 and an initial concentration range of 20 -150 mgL-1. The equilibrium kinetic data supports a pseudo-second-order model, indicating chemisorption. BHC's potential as a sustainable adsorbent for water remediation was highlighted by the efficient Cr(VI) uptake supported by the combined mechanisms of electrostatic attraction, surface complexation, and reduction.